Characterization and mechanical properties of coconut shell filled acrylonitrile butadiene styrene / ethylene propylene diene monomer composites - Siti Noorkhartina, Ishak (Universiti Malaysia Perlis, 2011)
Coconut shell filled ABS/EPDM composites were prepared using a Z-blade mixer at processing temperature 2000C and rotor speed 50rpm.Effect of chemical treatment,different composition of blend ratio , different filler loading and effect of thermal aging on mechanical, thermal, and morphological properties of coconut shell filled ABS/EPDM composites was investigated.Maleic acid (MA) were used to treat the fiber surface.The increasing composition of EPDM will decrease the tensile strength and Young’s modulus but increasing in elongation at break.The increasing in filler loading and the presence of maleic acid increase the tensile strength and Young’s modulus but decrease the elongation at break is decreased.Result after thermal aging shows the same trend but lower than before aging.Morphological investigation using SEM revealed that the improvement in tensile strength and Young’s modulus was due to enhancement of the interfacial adhesion between coconut shell and ABS/EPDM. The thermal stability of coconut shell filled ABS/EPDM blends improved with the presence of MA.